A novel PKHD1 splicing variant identified in a fetus with autosomal recessive polycystic kidney disease - Miao, Mingzhu; Feng, Liqun; Wang, Jue; Xu, Cheng; Su, Xiaotian; Zhang, Guoying; Lu, Shoulian (Frontiers in Genetics, 2023)
Objective: Variants of the polycystic kidney and hepatic disease 1 (PKHD1) gene are associated with autosomal recessive polycystic kidney disease (ARPKD). This study aimed to identify the genetic causes in a Chinese pedigree with ARPKD and design a minigene construct of the PKHD1 gene to investigate the impact of its variants on splicing.Methods: Umbilical cord samples from the proband and peripheral blood samples from his parents were collected, and genomic DNA was extracted for whole-exome sequencing (WES). Bioinformatic analysis was used to identify potential genetic causes, and Sanger sequencing confirmed the existence of variants within the pedigree.A minigene assay was performed to validate the effects of an intronic variant on mRNA splicing.Results: Two variants, c.9455del (p.N3152Tfs*10) and c.2408-13C>G, were identified in the PKHD1 gene (NM_138694.4) by WES; the latter has not been previously reported. In silico analysis predicted that this intronic variant is potentially pathogenic. Bioinformatic splice prediction tools revealed that the variant is likely to strongly impact splice site function. An in vitro minigene assay revealed that c.2408-13C>G can cause aberrant splicing, resulting in the retention of 12 bp of intron 23.A novel pathogenic variant of PKHD1, c.2408-13C>G, was found in a fetus with ARPKD, which enriched the variant spectrum of the PKHD1 gene and provided a basis for genetic counseling and the diagnosis of ARPKD. Minigenes are optimal to determine whether intron variants can cause aberrant splicing.